2015
DOI: 10.1111/wrr.12315
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of cutaneous wound healing by an FPR2‐specific peptide agonist WKYMVm

Abstract: Diabetes is one of the most common human diseases and 15% of the 200 million diabetics worldwide suffer from diabetic wounds. Development of new therapeutic agents is needed for treatment of diabetic wounds. Wound healing is mediated by multiple steps, including inflammation, epithelialization, neoangiogenesis, and granulation. Formyl peptide receptor 2 has been known to stimulate angiogenesis, which is essential for tissue repair and cutaneous wound healing. In this study, we explored the therapeutic effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
(36 reference statements)
0
22
0
Order By: Relevance
“…However, the expression of FPRs in various nonphagocytic cells suggests that these receptors also participate in functions other than innate immunity and may represent unique targets for therapeutic drug design [57]. Such drugs may have the potential to treat many inflammatory diseases, including rheumatoid arthritis, asthma, other auto-immune diseases, and stimulate wound healing [6, 810]. …”
Section: Introductionmentioning
confidence: 99%
“…However, the expression of FPRs in various nonphagocytic cells suggests that these receptors also participate in functions other than innate immunity and may represent unique targets for therapeutic drug design [57]. Such drugs may have the potential to treat many inflammatory diseases, including rheumatoid arthritis, asthma, other auto-immune diseases, and stimulate wound healing [6, 810]. …”
Section: Introductionmentioning
confidence: 99%
“…How FPR2 is able to recognize and bind these ligands and transduce both proinflammatory and anti-inflammatory signals remains a mystery. Some FPR2 ligands have shown therapeutic potential for the treatment of inflammation, diabetic wounds and Alzheimer's disease [7][8][9] . However, the lack of a three-dimensional structure of FPR2 has hampered the understanding of the potential therapeutic mechanism as well as their clinical applications.…”
mentioning
confidence: 99%
“…15 Recently, Kwon et al identified that the WKYMVm effectively stimulated the healing of a cutaneous wound in streptozotocin-induced diabetic mice. 9 By topical treatment with a small amount of WKYMVm (20 mL of 1 mM in HBSS) on wound sites for 12 days, they found that WKYMVm accelerated re-epithelialization and angiogenesis in dermal tissues. Histological analysis showed WKYMV-m-treated group accelerated re-epithelialization at the early time points compared with the HBSS-treated control group.…”
Section: Stimulation Of Cutaneous Wound Healingmentioning
confidence: 99%
“…6,7 In addition, several studies showed that WKYMVm improved tissue repair with enhanced neovascularization through promoting homing, proliferation, and tube formation of endothelial colonyforming cells (ECFCs). [8][9][10][11] Furthermore, synthesis of WKYMVm peptides composed of few amino-acids can be easily and quickly performed and cost-effective. With these properties of WKYMVm, recent studies are using these small peptides in various biomedical application fields.…”
Section: Introductionmentioning
confidence: 99%